Catapult effect in pole vaulting: Is muscle coordination determinant? - Frere, J.; Göpfert, B.; Hug, F.; Slawinski, J.; Tourny-Chollet, C. (Journal of Electromyography and Kinesiology, 2012)
This study focused on the phase between the time of straightened pole and the maximum height (HP) of vaulter and aimed at determining the catapult effect in pole vaulting on HP. Seven experienced vaulters performed 5-10 vaults recorded by two video cameras, while the surface electromyography (sEMG) activity of 10 upper limbs muscles was recorded. HP was compared with an estimated maximum height (HPest) allowing the computation of a push-off index. Muscle synergies were extracted from the sEMG activity profiles using a non-negative matrix factorization algorithm. No significant difference (p > 0.47) was found between HPest (4.64 ± 0.21 m) and HP (4.69 ± 0.23 m). Despite a high inter-individual variability in sEMG profiles, two muscle synergies were extracted for all the subjects which accounted for 96.1 ± 2.9% of the total variance. While, the synergy activation coefficients were very similar across subjects, a higher variability was found in the muscle synergy vectors. Consequently, whatever the push-off index among the pole vaulters, the athletes used different muscle groupings (i.e., muscle synergy vectors) which were activated in a similar fashion (i.e., synergy activation coefficients). Overall, these results suggested that muscle coordination adopted between the time of straightened pole and the maximum height does not have a major influence on HP.